2020
DOI: 10.3390/rs12010140
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Computational Intelligence Models for Improvement Gully Erosion Assessment

Abstract: Gullying is a type of soil erosion that currently represents a major threat at the societal scale and will likely increase in the future. In Iran, soil erosion, and specifically gullying, is already causing significant distress to local economies by affecting agricultural productivity and infrastructure. Recognizing this threat has recently led the Iranian geomorphology community to focus on the problem across the whole country. This study is in line with other efforts where the optimal method to map gully-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 78 publications
0
25
0
1
Order By: Relevance
“…Although it is difficult to directly compare the results of this study with those reported from other regions, we suggest that our ensemble models perform better than the generalized linear model (AUC = 0.71), boosted regression tree (AUC = 0.84), multivariate adaptive regression spline (AUC = 0.83), and ANN (AUC = 0.84) models used by Garosi et al [104]; the certainty factor model (AUC = 0.82) used by Azareh et al [82]; and the Fisher's linear discriminant analysis (AUC = 0.76), logistic model tree (AUC = 0.77), and NBT (AUC = 0.78) models of Arabameri et al [125]. In contrast, however, our models were outperformed by the maximum entropy (AUC = 0.88, 0.90) models used by Azareh et al (2019) and Kariminejad et al [107]; BFTree and its ensembles (bagging and RS) (AUC = 0.92) used by Hosseinalizadeh et al [81]; and the multivariate additive regression splines (AUC = 0.91), SVM (AUC = 0.88), and FR (AUC = 0.96) models employed by Gayen et al [126].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to directly compare the results of this study with those reported from other regions, we suggest that our ensemble models perform better than the generalized linear model (AUC = 0.71), boosted regression tree (AUC = 0.84), multivariate adaptive regression spline (AUC = 0.83), and ANN (AUC = 0.84) models used by Garosi et al [104]; the certainty factor model (AUC = 0.82) used by Azareh et al [82]; and the Fisher's linear discriminant analysis (AUC = 0.76), logistic model tree (AUC = 0.77), and NBT (AUC = 0.78) models of Arabameri et al [125]. In contrast, however, our models were outperformed by the maximum entropy (AUC = 0.88, 0.90) models used by Azareh et al (2019) and Kariminejad et al [107]; BFTree and its ensembles (bagging and RS) (AUC = 0.92) used by Hosseinalizadeh et al [81]; and the multivariate additive regression splines (AUC = 0.91), SVM (AUC = 0.88), and FR (AUC = 0.96) models employed by Gayen et al [126].…”
Section: Discussionmentioning
confidence: 99%
“…The area under receiver operating characteristics (AUROC) curve was used to test the various models. The AUROC curve is a threshold-independent tool for the measurement of predictive performance [101][102][103][104][105][106]. The AUROC indicates the model's predictive accuracy.…”
Section: Methods For Validating the Modelsmentioning
confidence: 99%
“…The multi-collinearity test is an important way to judge the linear dependency among the selected independent factors in the statistical modeling [44]. In the case of the machine learning models, this technique needs to be used for better results [45][46][47][48][49][50][51][52]. Researchers have applied multi-collinearity analysis for gully erosion susceptibility mapping [53], groundwater potentiality mapping [54], landslide susceptibility mapping [48] etc.…”
Section: Multi-collinearity Analysis Of Effective Factorsmentioning
confidence: 99%